Boosting photoprogramming performance of molecular-switch-embedded organic transistors via structural optimization of polymer semiconductors. Issue 4 (12th January 2023) - Yu, Seong Hoon; Hassan, Syed Zahid; Lee, Sangjun; Lim, Bogyu; Chung, Dae Sung
Abstract : A study on the crystallinity effect of polymer semiconductors on the photoprogramming performance of molecular-switch-embedded devices is proposed by optimizing the crystallographic compatibility between molecular switches and polymer semiconductors. Abstract : A herein, a synthetic strategy of polymer semiconductors to optimize compatibility with diarylethene (DAE)-based molecular switches and thus to maximize photoprogramming performances of the resulting DAE-embedded organic field-effect transistor (OFET) while maintaining high charge carrier mobility is suggested. We designed and synthesized a new copolymer, wherein carbazole is strategically introduced next to the thiophene-diketopyrrolopyrrole (DPP)-thiophene moiety to reduce overall coplanarity. Additionally, indacenodithieno[3, 2- b ]thiophene (IDTT) is introduced to induce high charge carrier mobility, similar to that of typical DPP-based copolymers. Comparative studies related to the structure, morphology, electronic and optoelectronic performances of conventional DPPT-TT and newly synthesized PCbD-IDTTP are systematically conducted to confirm the successful embedding of DAEs into the higher available volume of PCbD-IDTTP, resulting in not only well-preserved high charge carrier mobility but also outstanding photoprogrammable I DS ON/OFF ratios >10 3 of the resulting OFET. More importantly, even after 150 repeated photoprogramming steps, photoprogrammable I DS ON/OFF ratio maintains 10 3 . This work shows that not only the structures of DAE but also structure of the polymer semiconductor matrix is important for the development of high-performance photoprogrammable OFETs.